2006
DOI: 10.1111/j.1439-0434.2006.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resistance to Race 3, Biovar 2 of Ralstonia solanacearum in Tomato Germplasm

Abstract: Sources of resistance to tropical race 1 strains of Ralstonia solanacearum, the causative agent of bacterial wilt, have been identified in the tomato germplasm. Till now, no experimental data are available on Lycopersicon spp. (now Solanum spp.) sources for resistance to temperate race 3, biovar 2 strains. Eighty-two accessions belonging to different Lycopersicon spp. were evaluated for resistance to a race 3 strain endemic to Re´union Island. Evaluation was conducted in growth chambers, and included the Lycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…For disease control of bacterial wilt, planting resistance cultivars were screened and suggested. A few tomato cultivars had R. solanacearum resistance in recent studies (Carmeille et al, 2006;Han et al, 2009;Nakaho et al, 2004). However, changing resistant cultivars can sometimes lead to undesirable tomato traits.…”
Section: Discussionmentioning
confidence: 99%
“…For disease control of bacterial wilt, planting resistance cultivars were screened and suggested. A few tomato cultivars had R. solanacearum resistance in recent studies (Carmeille et al, 2006;Han et al, 2009;Nakaho et al, 2004). However, changing resistant cultivars can sometimes lead to undesirable tomato traits.…”
Section: Discussionmentioning
confidence: 99%
“…In Hawaii 7996, the movement of R. solanacearum is limited from the protoxylem into other xylem tissue, and this breeding line has been identified for future breeding programs in Japan (Nakaho et al, 2004). Hawaii 7996 has also been identified as a viable source of resistance for managing bacterial wilt caused by R. solanacearum (race 3, biovar 2) (Carmeille et al, 2006 problematic in many southeastern U.S. crops, including tomato, potato, tobacco, and eggplant. Control of BW in tomato is very difficult.…”
mentioning
confidence: 99%
“…In previous studies, Hawaii 7996 was found to be highly resistant when evaluated in fields located in 11 countries and territories (Wang et al 1997). However, it displayed partial resistance against a race 3/biovar 2/phylotype II strain isolated from potato in Reunion (Carmeille et al 2006b) and three strains of a new pathogenic variant of R. solanacearum named phylotype II/4NPB, described recently (Wicker et al 2007). Therefore, it is necessary to evaluate the new S. pennellii resistance sources reported here against strains with a wider diversity to determine their potential use.…”
Section: Discussionmentioning
confidence: 86%
“…More recently, partial resistance to a strain of race 3 biovar2 phylotype II was detected in one accession belonging to S. peruvianum, and one S. lycopersicon var. cerasiforme accession among the 82 accessions screened (Carmeille et al 2006b). Summarizing the results from previous studies, it may be worthwhile to more intensively evaluate the accessions of S. lycopersicon var.…”
Section: Discussionmentioning
confidence: 99%